Combining geographic information systems and regression models to generate locational value residual surfaces in the assessment of residential property values - Mar Iman, Abdul Hamid (PRRES, 2007)
Locational Value ResidualSurface (LVRS) has been suggested as an alternative to resolving the difficulty in the traditional modelling of locational influence on property values in a particular area. The objective of this paper was to compare the relative performance of models that apply locational value residual surface (LVRS) and the traditional multiple regression models in the prediction of residential property values. A controlled sample of 125 single- and double-storey residential properties was used to construct regression models. It was found that models applying LVRS were marginally better than the traditional models in predicting property values.